2022
DOI: 10.1038/s41597-022-01632-8
|View full text |Cite
|
Sign up to set email alerts
|

Global inventory of suitable, cultivable and available cropland under different scenarios and policies

Abstract: Where land-use change and particularly the expansion of cropland could potentially take place in the future is a central research question to investigate emerging trade-offs between food security, climate protection and biodiversity conservation. We provide consistent global datasets of land potentially suitable, cultivable and available for agricultural use for historic and future time periods from 1980 until 2100 under RCP2.6 and RCP8.5, available at 30 arc-seconds spatial resolution and aggregated at countr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 11 publications
(5 citation statements)
references
References 55 publications
0
5
0
Order By: Relevance
“…It appears that crop production generally concentrates on areas, where the suitability to grow crops is moderate or high as discussed in detail by Schneider et al (2022). Marginally suitable areas contribute 14% to the total crop protein, moderately suitable areas account for 66%, and highly suitable 15% (Fig.…”
Section: Crops' Potential To Produce Proteinmentioning
confidence: 91%
See 2 more Smart Citations
“…It appears that crop production generally concentrates on areas, where the suitability to grow crops is moderate or high as discussed in detail by Schneider et al (2022). Marginally suitable areas contribute 14% to the total crop protein, moderately suitable areas account for 66%, and highly suitable 15% (Fig.…”
Section: Crops' Potential To Produce Proteinmentioning
confidence: 91%
“…To identify areas where cropland expansion or reduction could occur, we utilized the suitability index (SI) approach (Zabel et al, 2014), which has also been employed in other studies (e.g., Cronin et al, 2020;Fodor et al, 2017;Foyer et al, 2019). For our analysis, we applied updated SI data (Schneider et al, 2022;Zabel et al, 2022). The SI measures the potential suitability of a given land area for agricultural use based on a range of local environmental conditions (climate, soil, topography).…”
Section: Redistribution Of Land Resourcesmentioning
confidence: 99%
See 1 more Smart Citation
“…To give insight on the resilience of Malawi's food system to this type of extreme events, we evaluate land and water availability to compensate for losses in these natural resources as a consequence of the floods. We gather areas available and suitable for agricultural expansion from (Schneider et al, 2022), and we use WATNEEDS (Chiarelli et al, 2020) to compute water scarcity, as the ratio between water demand (accounting for domestic, industrial and agricultural uses) and water availability (accounting for upstream uses and environmental flows).…”
Section: Methodsmentioning
confidence: 99%
“…To tackle this problem, scholars have been trying to combine LUCC data and different models to evaluate and simulate food security. Schneider et al (2022) predicted global future cropland resources under different climate paths based on existing LUCC data; Li S. et al (2023) built an analysis network based on LUCC data to assess regional grain production changes, and found that urbanization of the Loess Plateau will not endanger local food security; Sun et al ( 2023) built an early warning system for cultivated land resources based on LUCC data in order to achieve the sustainability of food security, economic development and ecological protection.…”
Section: Food Securitymentioning
confidence: 99%